2006
DOI: 10.1002/ccd.20848
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of novel biolimus eluting DEVAX AXXESS plus nitinol self‐expanding stent in a porcine coronary model

Abstract: BES favorably modulates the neointimal tissue formation for 28 days, in the porcine coronary model. Long-term inhibition of neointimal hyperplasia is not sustained most likely because of the delayed cellular proliferation and inflammation in the vessel wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The neointimal thickness for both XIENCE V and ML VISION remained stable from 180 days to 2 years, indicating that neointimal healing was complete by 180 days. As other DES systems, [CYPHER ® (Johnson and Johsn, Miami Lakes, FL), TAXUS, and ENDEAVOR ® (Medtronic Vascular, Inc., Santa Rosa, CA)] have not maintained neointimal suppression when compared to a bare metallic stent in preclinical models beyond 28 days, 7–11 the same quantitative trend was observed in these safety studies between XIENCE V and ML VISION.…”
supporting
confidence: 55%
“…The neointimal thickness for both XIENCE V and ML VISION remained stable from 180 days to 2 years, indicating that neointimal healing was complete by 180 days. As other DES systems, [CYPHER ® (Johnson and Johsn, Miami Lakes, FL), TAXUS, and ENDEAVOR ® (Medtronic Vascular, Inc., Santa Rosa, CA)] have not maintained neointimal suppression when compared to a bare metallic stent in preclinical models beyond 28 days, 7–11 the same quantitative trend was observed in these safety studies between XIENCE V and ML VISION.…”
supporting
confidence: 55%
“…The pattern and timing of injury after placement of an SE stent is different from that of the BE stents. Whereas BE stents achieve their final diameter immediately after the procedure, SE stents demonstrate ongoing expansion after their implantation, reaching their final diameter at a later time after the procedure (31). This characteristic might allow a gentler approach in the deployment of the self-expandable stent, to enable the accomplishment of optimal luminal volumes with less balloon barotrauma and consequently less IH formation.…”
Section: Discussionmentioning
confidence: 94%
“…CI ϭ confidence interval; HR ϭ hazard ratio. stent up to a predefined point, theoretically, decreasing the chronic injury and inflammation seen after the implantation of first-generation SE stents (31). The IVUS studies have demonstrated that the degree of final luminal diameter in vessels Ͻ2.75 mm in diameter is predictive of the likelihood of repeat revascularization (24).…”
Section: Discussionmentioning
confidence: 98%
“…These results may indicate adequate stent expansion over the stented segment within the small target coronary segments. Self‐expanding nitinol stents with continuous outward force on the vessel wall have been shown to cause positive remodeling and maintaining a lumen at stented site [11, 12], offering the possible platform for DES [13]. The procedure of Sparrow stent deployment caused neither stent edge dissection nor thrombus formation in this study.…”
Section: Discussionmentioning
confidence: 75%